Handgrip strength as a simple measure for screening prediabetes and type 2 diabetes mellitus risk among adults in Malawi: A cross‐sectional study. Issue 12 (1st November 2021) - Manda, Chrispin Mahala; Nakanga, Wisdom P.; Mkandawire, Joseph; Muula, Adamson S.; Nyirenda, Moffat J.; Crampin, Amelia Catherine; Wagatsuma, Yukiko
Abstract: OBJECTIVE: Handgrip strength, a simple measure of muscle strength, has been reported as a predictor of both prediabetes and type 2 diabetes mellitus (T2DM) and has been suggested for screening prediabetes and T2DM risk. This study examined the relationship of handgrip strength with prediabetes and T2DM among rural‐ and urban‐dwelling adults in Malawi. METHODS: This was a cross‐sectional study nested in a follow‐up study of prediabetic and prehypertensive individuals identified during an extensive noncommunicable disease survey in Malawi. A total of 261 participants (women: 64%) were recruited. Univariate and multivariate binary logistic regression analyses were performed to examine the association of prediabetes and T2DM with relative handgrip strength. RESULTS: The mean (SD) age of the participants was 49.7 (13.6) years, and 54.0% were between the ages of 40 and 59 years. The mean (SD) absolute handgrip strength and relative handgrip strength were 28.8 (7.3) kg and 1.16 (0.40) kg/BMI, respectively, and the mean relative handgrip strength differed significantly ( p < 0.001) by T2DM status. In unadjusted model, the odds ratio (OR) of prediabetes and T2DM per unit increase in relative handgrip strength was 0.12 [95% CI; 0.04–0.33]. The result remained significant after adjusting for age (continuous), sex, place of study, hypertension, dyslipidaemia and level of education (aOR [95% CI]; 0.19 [0.03–0.95]). CONCLUSIONS: The findings suggest that handgrip strength could be a relatively inexpensive, noninvasive measure for contributing to risk scores to identify high‐risk individuals for screening diabetes in SSA.